Allergic contact dermatitis from Solvent Orange 60 in spectacle frames. Issue 2 (9th April 2019) - Shono, Mamiko; Numata, Mitsuru; Sasaki, Kazumi
Abstract: Potential allergens in plastic spectacle frames concern plasticizers, antioxidants, UV filters, and dyes. Among the latter, Solvent Orange 60 (SO 60) has been recognized as an important allergen, and presently 32 cases have been reported in Japan and Scandinavia. In Japan, the first case of allergic contact dermatitis (ACD) from SO 60 in spectacle frames was reported in 1999, and 17 similar cases followed until 2018. Since 2006, 14 cases, observed among plastic production workers, and spectacle and dental goggle users, were reported in Scandinavia. This review provides a summary of the 18 Japanese cases of ACD from SO 60, the clinical manifestations, diagnostic method and results, provenance of causative spectacle plastic plates, as well as some countermeasures to prevent contact allergy to it. Abstract : Solvent Orange 60 (1% in petrolatum) provoked +++ vesicular reaction extending over 10 cm with infiltrative erythema and spreading. This review provides a summary of eighteen Japanese cases of allergic contact dermatitis from this dye, and some countermeasures to prevent contact allergy to it is discussed.